Safety assessment study of a planned offshore floating platform pipelaying test. (30th April 2018) - Ruan, Weidong; Bai, Yong; Zhang, Tianyu; Cao, Yu; Liu, Dahui
ABSTRACT: Serving as the most important component of a subsea production system, marine risers are one of the weakest and vulnerable marine structures. Therefore, the offshore pipelaying installation operation has been drawing more and more attention. In this paper, a safety assessment study of a planned offshore floating platform pipelaying test by reel-lay method is put forward. First, the real marine environment data and platform motion are collected in the field from the sea area. Then, tensile and bending tests of a flexible pipe are conducted to acquire its nonlinear tension-strain and moment-curvature mechanical properties. Later, based on the improved rod theory, the analyses of the flexible pipe's motion response under the offshore pipelaying operation are carried out by fully taking account of the irregular platform motion and hydrodynamic loadings caused by wave and current. Finally, a methodology for the flexible pipe offshore laying operation could be established.